Gas dynamics features of physico-chemical processes in the SRM large-sized charges at open firing - Alexander B. Vorozhtsov; Sergei S. Bondarchuk; Elizaveta V. Pikushchak; Sergei D. Sokolov (FirePhysChem, 2022)
The problem of utilization of solid rocket motors (SRM) with large-sized charges is a relevant objective. This is due to the decommissioning of SRM that failed or were rejected during production and operation, as well as with the implementation of strategic arms reduction treaties. Comparative analysis of SRM with large-sized charge utilization methods showed that the simplest, most productive, and relatively safe technique is open firing. At the same time, the information on the dynamics of harmful substances emission into the environment is needed to conduct quantitative assessment of the concentrations of environmentally hazardous combustion products formed during open firing. The calculation of intraballistic parameters in SRM makes it possible to estimate the consumption parameters of harmful gaseous and condensed combustion products entering the atmosphere. Also, it allows analyze the spatial and temporal course of the concentrations of these substances and optimize ways to reduce environmental hazards. The mathematical model and results of gas dynamics parameters calculation at the open firing of large-sized SRM with the demounted nozzle unit and forward bottom are submitted. The key features of realized flow modes are marked: significant pressure differentials along the length of the SRM in the initial stage of its activity; transonic velocities of intrachannel flow; erosion effects on the initial stages of burning rate.